Structure and AC impedance analysis on nanostructured LaFeO3 Perovskites - Gómez Cuaspud, Jairo Alberto; Neira Guío, Ariatna Yizel (2021)
Several compounds have been suggested for use in Solid Oxide Fuel Cells, mainly for anodes, because they are responsible for the oxidation reaction progress between fuel and oxygen ions (O2). Actually, there is a great interest in synthesizing new and alternative materials for anodes, such as perovskites, fluorites, ruthenium oxides, pyrochlores and nickel cermets. Typically, porous cermets of nickel and yttria stabilized zirconia (Ni/YSZ) have been extensively studied for several years and represent the current state of art of anodic materials for solid oxide fuel cells, due to its low cost, high electrical conductivity, chemical stability, and thermal expansion coefficient. The properties of these anodes are highly dependent on the particle size and microstructure of the cermet, showing that the synthesis conditions and chemical routes play an important role improving catalytic properties, as shown by Ribeiro et al [1].